Meaning Values of Anxiety in Women with Disorders in Reproductive Sphere - M Yu Norina (Peoples' Friendship University of Russia (RUDN University), 2012)
The article is dedicated to detecting the meanings of anxiety in women with reproductive disorders, which allows us to determine the «targets» of psychotherapy. The choice of self-actualization direction is important for pregnant women. The anxiety is associated with the refusal of professional realization. The meaning of normal anxiety is the confrontation with life difficulties. The meanings of pathological anxiety are avoiding difficulties, a passive position, the feeling of powerlessness.